Genetic identification of the local mukodamashi varieties of foxtail millet (Setaria italica (L.) P. Beauv) in Japan. (3rd April 2022) - Kato, Futoshi; Nashima, Kenji; Sasaki, Futoshi; Kurauchi, Nobuyuki
ABSTRACT: Different varieties of foxtail millet ( Setaria italica (L.) P. Beauv) are grown in Japan; there are several varieties of Mukodamashi, and they are cultivated in more than 10 prefectures. However, while most of Mukodamashi varieties have white grains and waxy endosperms, it is uncertain whether they have the same or different genotypes. In this study, five Mukodamashi varieties, from Gunma, Miyazaki, Ehime, Kochi, and Nara Prefectures, as well as 23 other local varieties of foxtail millet, were examined using simple sequence repeat markers to elucidate their genetic identities. The five Mukodamashi varieties have different genotypes. Therefore, we concluded that different varieties in different areas have been named Mukodamashi . It is possible that local varieties with the same name are actually different varieties, even if they have similar characters. Graphical Abstract: uf0001